Prevalence of falls, injury from falls and associations with chronic diseases among community-dwelling older adults in Guangzhou, China: a cross-sectional study - Wei-Quan Lin; Wei-Quan Lin; Lin Lin; Si-Yu Sun; Le-Xin Yuan; Min-Ying Sun; Min-Ying Sun; Chang Wang; Jia-Min Chen; Yao-Hui Li; Qin Zhou; Di Wu; et al. (Frontiers Media S.A., 2023)
IntroductionAs a developing country with the largest older adult population in the world, strengthening the research on falls among the older adults is undoubtedly an urgent item in China. This study aimed to explore the prevalence and risk factors associated with falls and injury from falls among community-dwelling older adults in Guangzhou, China, particularly focusing on their associations with chronic diseases.MethodsA total of 1,629 participants aged 65 years and above were selected from 11 counties in Guangzhou by the multi-stage stratified random sampling method in 2021. Socio-demographic characteristics, health and lifestyle factors, the status of falls, and injury from falls were measured by structured questionnaires through face-to-face interviews. Chi-square tests and logistic regression analysis were used to identify factors associated with falls and injury from falls. Chord diagrams were used to explore their associations with chronic diseases.ResultsA total of 251 participants (15.41%, 95% CI: 13.98%−17.25%) reported falls, and 162 participants (9.46%, 95% CI:7.72%−11.55%) indicated an injury from falls. Logistic regression analysis showed the results as follows: female patients (adjusted OR = 1.721, 95% CI: 1.681-1.761) aged ≥80 years (1.910, 1.847-1.975), unemployed (1.226, 1.171-1.284), uninsured (1.555, 1.448-1.671), average monthly household income of 2,001-4,000 CNY (1.878, 1.827-1.930), number of services provided by the community health center ≥13 times per year (1.428, 1.383-1.475), illness within 2 weeks (1.633, 1.595-1.672), high-intensity physical activity (2.254, 2.191-2.32), sedentary (1.094, 1.070-1.117), and number of chronic disease illnesses ≥3 (1.930, 1.870-1.993). Meanwhile, those risk factors were also associated with injury from falls. The older adults with medium-intensity physical activity were at lower risk (0.721, 0.705-0.737) of falls and higher risk (1.086, 1.057-1.117) of being injured from falls. Chord diagrams showed the correlations between chronic diseases and falls and injury from falls among community-dwelling older adults in Guangzhou, China.ConclusionThe high prevalence of falls is found among community-dwelling older adults in Guangzhou, China, which is related to multiple factors such as demographic variables, lifestyle, and health status, especially for chronic diseases. Therefore, targeted interventions should be developed and implemented urgently.